Sharia insurance efficiency in Indonesia and Malaysia using the stochastic frontier approach analysis - Zubaidah Nasution (Asian Journal of Islamic Management, 2022)
Purpose: This study aims to analyze the efficiency level of Indonesian sharia insurance and Malaysian takaful with a parametric stochastic frontier approach where the input is total assets and expenses, and the output of this research is claims and premiums.